(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2014)
This paper attempts to explain occurrences of psychosis through a new understanding: as a coping mechanism. This hypothesis seems to have broad explanatory power. Some qualitative evidence also supports this understanding. This paper concludes that it is possible to understand psychotic episodes as mechanisms for coping with existential distress.